The grid mat method to increase bearing capacity of subgrade soil - Kassim, Fauziah; Khatib, Anwar; Yusof, Mohd. Zain; Marto, Aminaton (Faculty of Civil Engineering, 2004)
The investigation will be conducted on cohesive soil produced from kaolin powder. The grid mat will made by different shapes, i.e., triangular and square, and made of materials such as steel. Each model testing will consist of two stages; consolidation stage and loading stage. In the consolidation stage, the soil will be double drained whereby the loading plate will be drilled to from holes of about 5mm diameter so that drainage can occur through the loading plate as well. During loading stage, the soil deformation is to be monitored using at least two LVDT while the loading is measured using the load cell attached at the top loading platen. The LVDT and the load cell will be attached to a readout unit which will either be a data logger or an ADU connected to a computer.